THE ACCULTURATION OF KABA IN RANDAI UDA DAN DARA 2022: PEMBUDAYAAN MIGRASI KABA DALAM TEATER RANDAI UDA DAN DARA 2022 - Ayu Haswida Abu Bakar,; Duratul Ain Dorothy Jonathan Linggang ,; Norzizi Zulkafli, (Jurnal Pengajian Melayu (JOMAS), 2024)
ABSTRACT Randai is one of the traditional Minangkabau cultures originated from West Sumatra, Indonesia. Characterised by drama, kaba, dance, song and silat. Thus, Randai refers to Minangkabau custom and cultural heritage. Therefore, kaba can be found in the form of stories, songs, rituals, mythologies, and folklores of these communities. Even with the increasing population of the Minangkabau Diaspora, especially in Negeri Sembilan since the early 19th century, randai remains as Minangkabau heritage culture. Hence has adapted some of Malay stories, songs, rituals, mythologies, and folklore of Negeri Sembilan community that has similarities with the story in West Sumatra. The novelty of this paper is to explore the acculturation of kaba in Randai performance, defined as Minangkabau culture, which researchers have not widely studied. The study of acculturation in Minangkabau Kaba has never been published. It is a qualitative approach via content analysis. Rest on the notion of kaba which is defined as a story. The research draws on the concept of acculturation of the story of Uda dan Dara by Usman Awang in Randai Uda dan Dara 2022 performance. The result highlights Uda dan Dara as kaba to a certain extent can be seen as a manifestation of a creative adaptation through the concept of acculturation. Thus, functions as a new set of meaning to Randai. Keywords: Randai; Kaba; Acculturation; Uda dan Dara; Randai Uda dan Dara 2022 ABSTRAK Randai adalah salah satu budaya tradisional Minangkabau yang berasal dari Sumatera Barat, Indonesia. Bercirikan drama, kaba, tarian, lagu dan silat. Justeru itu, randai merujuk kepada adat dan warisan budaya Minangkabau. Maka, kaba boleh didapati dalam bentuk cerita, lagu, ritual, mitologi, dan cerita rakyat masyarakat ini. Walaupun dengan pertambahan penduduk diaspora Minangkabau khususnya di Negeri Sembilan sejak awal abad ke-19, Randai kekal sebagai budaya warisan Minangkabau. Melalui migrasi, pembudayaan berlaku melalui proses adaptasi beberapa cerita Melayu, lagu, ritual, mitologi, dan cerita rakyat Negeri Sembilan yang mempunyai persamaan dengan cerita di Sumatera Barat. Fokus kertas kerja ini adalah untuk meneroka pembudayaan kaba dalam persembahan Randai, yang ditakrifkan sebagai budaya Minangkabau, yang belum dikaji secara meluas oleh penyelidik. Kajian pembudayaan kaba randai Minangkabau adalah pendekatan kualitatif melalui analisis kandungan. Berpegang pada pengertian kaba yang ditakrifkan sebagai cerita. Kajian ini menggunakan konsep pembudayaan kaba teater Randai melalui cerita Uda dan Dara oleh Usman Awang dalam persembahan Randai Uda dan Dara 2022. Hasilnya Uda dan Dara sebagai kaba dilihat sebagai manifestasi adaptasi kreatif melalui konsep pembudayaan migrasi. Oleh itu, berfungsi sebagai satu set makna baru kepada kaba teater Randai Minangkabau. Kata kunci : Randai; Kaba; Pembudayaan; Uda dan Dara; Randai Uda dan Dara 2022